The effectiveness of Electronic Word-of-Mouth (eWOM) on consumer purchase intention among Generation-Y - Lim Jiea Wern; Nor Khairul Nisa Sarafudin; Nor Shafira Norhisham; Nur Ezete Fazlina Zulkifli (2016)
The purpose of the study is to develop a conceptual framework on the effectiveness of electronic word-of-mouth (eWOM) towards consumer purchase intention among Generation-Y. eWOM is something that shows people especially online consumers’ reviews regarding product they purchased which help others in e-commerce purchasing decisions. Those feedbacks help consumers to determine how effective the information is in social media. Questionnaire used to collect the data and allow the researcher to go through multiple regression analysis that elaborates the relationship between quality, quantity, credibility, sender’s expertise and purchase intention towards Gen-Y before making any purchases. The study focuses on the Gen-Y since that generation perceived as growingly familiar with digital and electronic technology. A survey was conducted among 370 respondents of Gen-Y aged between 18 to 35 years. This study has found that consumer purchase intention has positive associations with eWOM quality, eWOM quantity, eWOM credibility and sender’s expertise.